Neurology Training Worldwide - Hillis, James M.; Berkowitz, Aaron L. (Seminars in Neurology, 2018)
Neurology training is essential for providing neurologic care globally. Large disparities in availability of neurology training exist between higher- and lower-income countries. This review explores the worldwide distribution of neurology training programs and trainees, the characteristics of training programs in different parts of the world, and initiatives aimed at increasing access to neurology training in under-resourced regions.
Keywords: global health; neurology; medical education